Distribution of sand flies (Diptera: Psychodidae) at different altitudes in an endemic region of American cutaneous leishmaniasis in the State of Espírito Santo, Brazil - Adelson Luiz Ferreira; Paulo Augusto Sessa; José Benedito Malta Varejão; Aloísio Falqueto (Memorias do Instituto Oswaldo Cruz, 2001)
The involvement of different sand fly species in the transmission of American cutaneous leishmaniasis (ACL) at different altitudes was evaluated in the municipality of Afonso Cláudio in the State of Espírito Santo, Brazil, from November 1995 to February 1997. CDC light traps and Shannon traps baited with human volunteers were hung simultaneously at three altitudes of a river valley: (a) 650-750 m in an area of active ACL transmission; (b) 750-850 m in a transitional area; and (c) 850-950 m in an area where no ACL transmission occurred. A total of 13,363 specimens belonging to 28 species was collected. The five most abundant man-biting species were Lutzomyia intermedia, which constituted 24.3% of the total, Lu. migonei (22.3%), Lu. whitmani (15.4%), Lu. fischeri (14.9%) and Lu. monticola (5.8%). Analysis of the distribution of these species at the three altitudes provided evidence that Lu. fischeri and Lu. monticola were not involved in ACL transmission, whereas Lu. migonei and Lu. whitmani might act as secondary vectors of Leishmania (Viannia) braziliensis and Lu. intermedia was probably the principal vector of the parasite. These results reinforce those published in the existing literature, which indicate that Lu. intermedia is the main vector of Le. (V.) braziliensis in Southeast Brazil, while Lu. migonei and Lu. whitmani are of secondary importance.